2023
DOI: 10.1590/0103-8478cr20210722
|View full text |Cite
|
Sign up to set email alerts
|

Recommendation of soil fertilization with copper and zinc for soybean crops grown in Petric Plinthosol

Abstract: Cultivation of soybean and off-season corn is advancing in areas under restricted edaphoclimatic conditions, such as petric plinthosols, which have significant proportions of gravel and are deficiency in micro-nutrients such as copper (Cu) and zinc (Zn). The effects of Cu and Zn concentrations on soybean nutrition cultivated in petric plinthosol are unclear, and it is unknown whether the levels considered adequate for other soils are sufficient for gravely soils, or even if higher Cu and Zn rates can cause a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…The deficiency of this element also affects chlorophyll, and this can be observed as leaf chlorosis [39]. Almeida et al [40] demonstrated that high doses of Cu and Zn did not have toxic effects on soybean crops. Yasari and Vahedi [41] showed that foliar Zn fertilisation had good results in soybean crops.…”
Section: Discussionmentioning
confidence: 99%
“…The deficiency of this element also affects chlorophyll, and this can be observed as leaf chlorosis [39]. Almeida et al [40] demonstrated that high doses of Cu and Zn did not have toxic effects on soybean crops. Yasari and Vahedi [41] showed that foliar Zn fertilisation had good results in soybean crops.…”
Section: Discussionmentioning
confidence: 99%